EFFECTIVENESS OF HYPNOTHERAPY IN INSOMNIA PATIENTS: SYSTEMATIC LITERATURE REVIEW - Dyah Pradnyaparamita Duarsa; Cokorda Bagus Jaya Lesmana; Ariana, Putu Agus; I Made Ady Wirawan (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Insomnia is a sleep disorder that is often a complaint in the elderly which ischaracterized by difficulty sleeping and maintaining sleep. There are various recommendedtherapies for the management of insomnia. One of the therapies used was hypnotherapywhich aimed to find out, compare and analyze hypnotherapy as an intervention inInsomnia. Method. This study used a systematic review design, following guidelinesdescribed by the Preferred Reporting Items for Systematic Review and Meta-Analysis(PRISMA). The library source search was conducted online using the Google Scholar,Pubmed, and Science Direct databases. The keywords used are "effectivity","hypnotherapy", "insomnia". The literature search was limited to 2013 to 2021. 7 articleswere analyzed. The articles were selected using the inclusion criteria, namely full textarticles. Results&Analysis. Insomnia is still a health problem in the elderly. Variousattempts have been made to reduce the incidence of insomnia. Hypnotherapy can beapplied to therapeutic. Hypnotherapy provides benefits to reduce insomnia. Hypnotherapyin audio form can increase relaxation thereby reducing insomnia in the elderly.Discussion. Interventions carried out using hypnotherapy have potential in today's digitalera. Further research is needed to identify, develop and analyze a hypnosis-based insomniacontrol model on the index of insomnia, anxiety and sleep quality in the elderly. Inaddition, further research on the mechanism of cognitive therapy that plays a role in thecontrol model.